Evolutionary constraints of warning signals: A genetic trade-off between the efficacy of larval and adult warning coloration can maintain variation in signal expression. (1st November 2016) - Lindstedt, C.; Schroderus, E.; Lindström, L.; Mappes, T.; Mappes, J.
Abstract: To predict evolutionary responses of warning signals under selection, we need to determine the inheritance pattern of the signals, and how they are genetically correlated with other traits contributing to fitness. Furthermore, protective coloration often undergoes remarkable changes within an individual's lifecycle, requiring us to quantify the genetic constraints of adaptive coloration across all the relevant life stages. Based on a 12 generation pedigree with > 11, 000 individuals of the wood tiger moth ( Arctia plantaginis ), we show that high primary defense as a larva (large warning signal) results in weaker defenses as adult (less efficient warning color), due to the negative genetic correlation between the efficacy of larval and adult warning coloration. However, production of effective warning coloration as a larva did not incur any life-history costs and was positively genetically correlated with reproductive output. These results provide novel insights into the evolutionary constraints on protective coloration in animals, and explain the maintenance of variation in the signal expression despite the strong directional selection by predators. By analyzing the genetic and environmental effects on warning signal and life-history traits in all relevant life stages, we can accurately determine the mechanisms shaping the evolutionary responses of phenotypic traits under different selection environments.